Digital Green Finance Architecture in the Context of Green Deal Implementation: Modern Fintech Tools and Solutions Under the Sustainable Development Concept - Abramova, А.; Popelo, O.; Fedyshyn, M.; Popova, L.; Shchur, R.; Marych, M. (Journal of Lifestyle and SDGs Review, 2024)
Objective: The purpose of the article is to develop a scientific and applied toolkit, which is a set of a logically informationally and algorithmically interconnected means of the informationanalytical support of green financing within the Green Deal under the sustainable development concept. Theoretical Framework: The study is based on the Paris Climate Agreement, the European Green Agreement, and the concept of sustainable development. Method: To achieve the defined goal and solve the set tasks, a system of general scientific and special research methods was used. Results and Discussion: The author’s vision of the ecosystem model of the green financing is presented. The main trends of the global green bond market are identified; the parameters of the digital financing markets are estimated. The management decisions on accelerating the capital attraction and activation of green financing, ensuring the balance of the regional financing opportunities in the face of the global challenges are systematized. Research Implications: The important role of the state impact on the creation of the favourable conditions for the climate finance expansion by reducing the political, regulatory, control, macroeconomic and business risks has been established. It was established that the political stability, the consistent and clear regulatory framework, the agreed green financing policy and the openness to the international investors create the attractive conditions for the climate finance conditions. Originality/Value: Applying the author’s developments will create a basis for making the substantiated managerial decisions to the accelerated involvement of the capital in the green financing under the sustainable development concept.
Keywords: green Fintech ecosystem, financial services market, digital economy, insurtech, financial security, green digital technologies, financial instruments of sustainable development, sustainable development goals (SDGs).